Analisis Value For Money Dalam Mengukur Kinerja Keuangan: Studi Pada Dinas Perindustrian, Perdagangan Energi dan Sumber Daya Mineral Provinsi Sumatera Utara - Dila Wandasari; Aqwa Naser Daulay (Manajemen Kreatif Jurnal, 2023)
Any organization that adheres to established standard operating procedures, whether a business organization or a public institution, rewards good performance. The success of an organization depends on measuring its financial performance. The purpose of this research is to find out how value for money is in evaluating financial performance. The accountability report of the North Sumatra provincial government is used as secondary data in this research, which uses descriptive methodology with a quantitative approach. Data collection techniques include documentation methods. The results of this research show that the company's financial performance in 2022 is good in terms of Economic Ratios and Efficiency Ratios, but the Effectiveness Ratio cannot yet be considered effective performance.